Morbilidad respiratoria en los neonatos de término temprano, completo y tardío en el Hospital Regional Docente De Trujillo en los años 2011-2014 - Vilchez Senas, Cristian (2016)
Objective: Determine respiratory morbidity in term neonates. Patients and Methods: Descriptive study whose population were term neonates early, term full and term late borned between January 01, 2011 and December 31, 2014 by vaginal birth or cesarean section, they were hospitalized in the neonatology service of Regional Hospital of Trujillo. The frequency of various respiratory diseases was determined in groups of term neonates. Results: Of 148 neonates it found that the transient tachypnea of the newborn had a frequency of 42%, 42% and 16% in term neonates early, full term and late term respectively; hyaline membrane disease was 100%, 0%, 0% in term neonate early, full, and late respectively; meconium aspiration syndrome was 19%, 48%, 33% in term neonates early, full, late respectively. Conclusion: The most frequent respiratory disease in the group of term newborns early was the transient tachypnea of the newborn; and in the group of full term and late term were meconium aspiration syndrome